A Case of Nasal Glial Heterotopia That Can Be Misdiagnosed as Storiform Patterned Sclerotic Fibroma/Collagenoma - Fatma GUNDOGDU; Deniz ATES OZDEMIR; Ibrahim VARGEL (Federation of Turkish Pathology Societies, 2024)
Objective: Nasal glioma, also known as nasal glial heterotopia, is a rare tumor-like lesion that often affects newborns or infants with no hereditary predisposition. Case Report: A 4-year-old child with a growth on the nasal dorsum since birth was diagnosed with nasal glial heterotopia/nasal glioma. The lesion showed a sclerotic fibroma/collagenoma-like storiform pattern with entrapped glial tissue that was S100 and GFAP positive. Conclusion: When a biopsy of the nasal dorsum demonstrates sclerotic microscopic findings with a storiform pattern, nasal glioma should be considered before making a diagnosis in the collagen-rich tissue spectrum (collagenoma or Gardner's fibroma), and an immunohistochemical panel should be requested to demonstrate the presence of an unrecognized light microscopically visible glial component.